KAJIAN TENTANG PENATAAN KELURAHAN DAN DESA DI KECAMATAN TENGGARONG KABUPATEN KUTAI KARTANEGARA - Efri Novianto (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
This study is aimed at projecting the structuring of Kelurahan and Desa in Tenggarong Subdistrict, Kutai Kartanegara Regency and the inhibiting factors. The methods used are qualitative surveys and documentary studies with interactive analysis tools. The results of the study concluded that there were four Kelurahans that met the basic requirements and had the potential to be expanded, namely Jahab, Loa Ipuh, Loa Tebu and Mangkurawang. So that the arrangement of Kelurahan/ Desa is in accordance with the objectives and does not cause the conflict, this study recommends that the government conduct socialization on the objectives, procedures, requirements and administrative arrangements regarding the structuring of Kelurahan/ Desa, completes a map of boundaries between Desa or between Kelurahan, and conducts mapping the demographic (the population) an aspect of the Kelurahan/ Desa that will be reorganized.